TYPOLOGY OF CODING SYSTEMS IN GRAPHIC DESIGN - VOROBCHUK, M. S.; PASHKEVYCH, K. L. (Art and Design, 2022)
The aim of the study is to develop a typology of coded information, namely for barcode and QR-code, for further application in design. Methodology. Analytical, structural, and complex approaches, as well as art history methods, including comparative analysis, have been used. Results. The analysis of coded information has been carried out, the typology of coding systems for different types of design has been developed on the basis of the analysis. The functional purpose of barcode and QR-code has been studied. Methods, types, and ways of coding information have been defined. It has been found that coded information with the help of various additions and transformations determines the nature of object perception in different spheres of human life and the variability of their use. Particular attention is paid to the use of code in various types of design. The analysis of coded information in different types of design is presented. The sequence of development of the artistic and graphic process of code creation has been traced. The importance of using coded information for further formation and improvement of design objects has been proved. Scientific novelty. For the first time, a typology of coded information for different types of design has been developed. Practical significance. Types and kinds of coded information are described, ways of its visualization are allocated. The results of the study can be used for further study of coded information, as well as serve as a theoretical and practical material for the training of design professionals.